PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN BENGKEL CAHAYA TERANG DI BUNGKU TENGAH - KORO, MOH. SANDY ANDI (Fakultas Ekonomi Universitas Tadulako, 2019)
This research aims to find out and analyze the influence of the quality of services towards customer satisfaction workshop of Cahaya Terang. This type of descriptive research is causal, using the technique of sampling method of accidental sampling. Data collection was done by disseminating a questionnaire to 90 people or respondents who coincidentally met in the workshop of CahayaTerang. Primary Data obtained from the results of the responses of the respondents through questionnaires, observation and dissemination.Analysis tools are used multiple linear regression analysis to test the variable with the help of the program SPSS Version 16.0. The results showed that the quality of service of influence simultaneously towards customer satisfaction. Physical evidence of the influential variables are partial and significantly to customer satisfaction. Variable reliability effect partially but not significant toward customer satisfaction. The variable responsiveness effect partially but not significant toward customer satisfaction. Influential guarantee partially variable and significantly to customer satisfaction. Empathy and variable effect in partial and significantly to customer satisfaction.This research aims to find out and analyze the influence of the quality of services towards customer satisfaction workshop of Cahaya Terang. This type of descriptive research is causal, using the technique of sampling method of accidental sampling. Data collection was done by disseminating a questionnaire to 90 people or respondents who coincidentally met in the workshop of CahayaTerang. Primary Data obtained from the results of the responses of the respondents through questionnaires, observation and dissemination.Analysis tools are used multiple linear regression analysis to test the variable with the help of the program SPSS Version 16.0. The results showed that the quality of service of influence simultaneously towards customer satisfaction. Physical evidence of the influential variables are partial and significantly to customer satisfaction. Variable reliability effect partially but not significant toward customer satisfaction. The variable responsiveness effect partially but not significant toward customer satisfaction. Influential guarantee partially variable and significantly to customer satisfaction. Empathy and variable effect in partial and significantly to customer satisfaction.